(3GSS GdeQGLYI GdNGQLjI (B/s - (3GdUMf, YHO GdaJGM eMeOs; (3MSf, CMeO YHjOs ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2007)
(3ebOeI aj NOeGJ GdJCcjO Gdegfj hGdeQGLYI,GdEWGQ Gdegfj ddeQGLYI,GdeSFhdjI GdbGfhfjI ddeQGLY,eQGLYI GdCUhd GdKGHJI,eQGLYI GdfbOjI hYedjGJ GdebHhVGJ hGdeOahYGJ,eQGLYI GdeNRhf,eQGLYI GdNUhe,JbQjQ eQGbH GdMSGHGJs
Keywords: (3eQGLYI GdMSGHGJs